Chinese herbal medicine formulas as adjuvant therapy for osteonecrosis of the femoral head: A systematic review and meta-analysis of randomized controlled trials. Issue 36 (September 2018) - Zhang, Qingwen; Yang, Fan; Chen, Yaolong; Wang, Haibin; Chen, Delong; He, Wei; Chen, Peng
Abstract: Background: Osteonecrosis of femoral head (ONFH) is a disabling clinical entity affecting mainly young adults. Although Chinese Herbal Medicine (CHM) has been widely used as an adjunct therapy for ONFH in China, its effectiveness is not well defined. The purpose of this systematic review is to assess the effectiveness of CHM as an adjunct therapy to core decompression (CD) for patients with ONFH. Methods: A systematic literature search was conducted in 10 electronic databases. Randomized controlled trials involving CHM and CD for ONFH were included. Two authors independently assessed the studies for inclusion and extracted the data. A meta-analysis was conducted to estimate the safety and efficacy of CHM as an adjunct therapy. Results: Twenty-three randomized controlled trials with 1815 participants were included. The formulas used in these studies were different and we only combined data of studies observing the same formulas. Patients treated with CHM additionally exhibited a better TER (total effective rate) compared with CD alone in different degree, with the risk ratio (RR) varies from 1.09 to 1.09. The Harris score and radiographic effective rate indicate a similar result, with the medicine (MD) varies from 17.35 to 14.94 and RR 1.40 to 1.27. The risk of side-effect was barely reported except only 2 study record that no complications were observed. Conclusion: This systematic review indicated that CHM as adjunctive therapy may improve the effectiveness of CD. However, a firm conclusion could not be reached because of overall high risk of bias in most domains. Further studies of higher quality are required, and other benefits of CHM remain to be determined. Abstract : Supplemental Digital Content is available in the text